Fair financing in Germany's public health insurance: income-related contributions or flat premiums - Heinz Rothgang; Mirella Cacace (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2005)
Social justice in health care insurance relates to both, the utilisation of services and the financing of the system. With respect to the latter, in its World Health Report 2000 the WHO promoted a concept of fair financing that asks for contributions to health care financing that are proportional to households' capacity to pay. This claim contains three dimensions: the rejection of risk-related premiums, the claim that all households with equal income should pay equal premiums (horizontal justice), and the suggestion that higher income should lead to proportionally higher premiums (vertical justice). In this paper we first discuss the normative dimension of fair financing and develop a slightly modified version of the WHO's normative framework. Second, empirical findings based on WHO data and on data from the ECuity project are presented for selected countries. While the WHO concept does not allow drawing unambiguous conclusions, the latter shows, that Germany's system is regressive. With respect to the normative framework developed we can therefore conclude that future reforms should make the system more progressive. Against this background, two recent alternative strategies for reforming health financing, the Bürgerversicherung and the Gesundheitsprämie, are discussed. While both reform options are to be judged as more or less equivalent regarding horizontal justice and the rejection of risk-related premiums, some evidence is given towards the inferiority of the Gesundheitsprämie model with respect to vertical justice.
Keywords: 320; Gesetzliche Krankenversicherung; Gesundheitsreform; Gesundheitsfinanzierung; Kopfsteuer; Deutschland